NIKAH BEDA AGAMA DI INDONESIA: STUDI KOMPARASI HUKUM ISLAM DAN HUKUM NASIONAL - Amiruddin, Amiruddin (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2024)
This research is aiming at discussion about different religious marriage in Indonesia by comparing Islamic law perspective and national law. However, this kind of marriage has been a trend among society in Indonesia recently, mostly performed by the artists. By using library research as the method and synthesis approach for the analysis, this article would like to strengthen the mainstream view that prohibit marriage among different religious adherents, either by Islamic law or by national law norms. As the conclusion, this article finds that the rule which prohibit this kind of marriage among people in Indonesia should be inforced in order to build mutual harmony of life within society.